1993
DOI: 10.1016/0735-1097(93)90044-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of early intravenous treatment with a beta-adrenergic blocking agent or a specific bradycardiac agent in patients with acute mycardial infarction receiving thrombolytic therapy

Abstract: In the absence of contraindications, the administration of a beta-blocker or a specific bradycardiac agent together with thrombolytic therapy was safe. In this limited number of patients, these agents did not appear to enhance myocardial salvage or preservation of left ventricular function or to reduce the incidence of major arrhythmias in the early phase of infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
4

Year Published

1994
1994
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 34 publications
0
39
0
4
Order By: Relevance
“…Moreover, alinidine-treated patients tended to have smaller infarcts compared with placebo and atenolol patients. 7 The trend toward a higher incidence of AIVR in the active treatment groups can be explained by the bradycardiac effect, which increases the probability of AIVR to break through the sinus rhythm, and does not appear to be the expression of a proarrhythmic effect. The same observation was made in the TIMI 1I-B trial.6 Remarkably, the rate of the AIVR runs was not changed by /3-blocker therapy or by alinidine.…”
Section: Sustained Ventricular Tachycardia and Ventricular Fibrillationmentioning
confidence: 99%
“…Moreover, alinidine-treated patients tended to have smaller infarcts compared with placebo and atenolol patients. 7 The trend toward a higher incidence of AIVR in the active treatment groups can be explained by the bradycardiac effect, which increases the probability of AIVR to break through the sinus rhythm, and does not appear to be the expression of a proarrhythmic effect. The same observation was made in the TIMI 1I-B trial.6 Remarkably, the rate of the AIVR runs was not changed by /3-blocker therapy or by alinidine.…”
Section: Sustained Ventricular Tachycardia and Ventricular Fibrillationmentioning
confidence: 99%
“…No entanto, esses estudos foram conduzidos antes da era dos fibrinolíticos e da angioplastia primária, o que não representa o universo global de pacientes que são atendidos com IAM. Dois estudos randomizados 313,314 com betabloqueadores intravenosos foram avaliados após o uso rotineiro dos fibrinolíticos, porém o número de eventos foi muito pequeno para se chegar a conclusões. Já no estudo TIMI-2 (Thrombolysis in Myocardial Infarction) 315 , os pacientes submetidos a trombólise e randomizados para o uso de metoprolol intravenoso tiveram menor incidência de reinfarto e isquemia recorrente.…”
Section: -Betabloqueadoresunclassified
“…Among those treated especially early (ie, within 2 h of symptom onset), the composite endpoint of death or reinfarction occurred less often in those given immediate IV metoprolol than in those who did not receive it. The benefits of routine early IV use of β-blockers in the fibrinolytic era have been challenged by 2 later randomized trials of IV β-blockade 7, 8 and by a post hoc analysis of the use of atenolol in the GUSTO-I trial. 9 A subsequent systematic review of early β-blocker therapy for STEMI found no significant reduction in mortality.…”
Section: Article P 439mentioning
confidence: 99%